Water Purification (IntechOpen, 2024)
Water covers 70% of the Earth, but only 3% of it is drinkable, and most of this water (2%) is not accessible because it is locked in ice caps, glaciers, or the soil. Globally, 2.7 billion people experience water scarcity for at least one month of the year, while around 1.1 billion people lack access to water. In this book, scientists and entrepreneurs from the five continents present their ultimate expertise to address the crisis. The book comprises twelve chapters that present case studies from different parts of the world and industrial products for water purification, desalination, and energy production.